A Terrestrial‐Aquatic Model Reveals Cross‐Scale Interactions Regulate Lateral Dissolved Organic Carbon Transport From Terrestrial Ecosystems. Issue 5 (13th May 2022) - Talbot, Ceara J.; Bolster, Diogo; Medvigy, David; Jones, Stuart E.
Abstract: Lateral carbon transport (LCT), the flux of terrestrial C transported to aquatic ecosystems, displaces carbon (C) across the terrestrial‐aquatic continuum and is on the same order of magnitude as terrestrial net ecosystem production. However, few continental scale C models include LCT or the C‐hydrology linkages necessary for modeling LCT. Those that do exist, borrow processes and conceptual understanding from watershed scale models, assuming that large‐scale and small‐scale drivers of LCT are the same. We develop a conceptual framework of LCT, which focuses on lateral dissolved organic carbon (DOC) transport (LCT‐DOC), and operationalize it with a coupled terrestrial‐aquatic C and hydrology model. After comparing our model LCT‐DOC to previous estimates derived from a summation of landscape scale fluxes for the Contiguous U.S., we use model experiments to partition the importance of LCT‐DOC drivers including total annual precipitation, air temperature, and plant traits, which interact across regional and local scales. We find that climate is the strongest driver of LCT‐DOC, where LCT‐DOC is positively related to precipitation but inversely related to temperature at continental scales. However, the net effect of climate on LCT‐DOC is the product of cross‐scale interactions between climate and vegetation. Plant traits also interact strongly with climate and have a measurable influence on LCT‐DOC, with water use efficiency as the most influential plant trait because it couples terrestrial water and C cycling. We demonstrate that our conceptual framework and relatively simple linked C‐hydrology process model of LCT‐DOC can inform hypotheses and predict LCT‐DOC. Plain Language Summary: Runoff from land transports carbon (C) to nearby streams, rivers, and lakes, where it can be decomposed, stored, or transported further downstream. This lateral carbon transport (LCT) can be as large as annual storage of carbon in soil and moves C across the landscape. Much of our understanding of what controls LCT comes from small, location‐focused studies and many mathematical models used to understand this important process are also location‐specific. To understand LCT at large, continental scales, we must consider drivers that vary at those larger scales, such as vegetation type and climate, and incorporate those drivers into mathematical models. In this study, we develop a conceptual framework for LCT production and a mathematical model that integrate impacts of climate, plant characteristics, and interactions between them. We find that interactions among precipitation, temperature, and plants regulate LCT production at a continental scale. Key Points: Created a new conceptual framework for understanding lateral DOC transport (LCT‐DOC) from terrestrial ecosystems at continental scales Operationalized our conceptual framework with a simple coupled terrestrial‐aquatic hydrology and carbon process model Identified cross‐scale interactions among climate (i.e., precipitation) and plant trait drivers of LCT‐DOC